The effects of market concentration, trade, and FDI on total factor productivity: evidence from Indonesian manufacturing sector - Lilik Sugiharti,; Rudi Purwono,; Miguel Angel Esquivias,; Teguh Sambodo, Leonardo A.A.; Samuel Kharis Harianto, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study empirically examines the effects of exports, imports, market concentration, and foreign direct investment (FDI) on total factor productivity (TFP). We use a sample of 18,002 Indonesian manufacturing firms, categorized according to technology intensity of low, medium, and medium-high over 2010-2014. TFP and its sub-components, e.g., technical efficiency, technological progress, and scale effect, are estimated using a Malmquist Productivity Index (MPI). The estimation results indicate that market concentration, trade, and FDI positively impact technical efficiency and production scale, but reduce technological progress, which inhibits sectoral development. FDI inflows in Indonesia increase technical efficiency but negligibly enhance technological competencies and the scale of operation in recipient sectors. Increasing firm size is crucial in achieving greater productivity. An increase in market concentration has a negative effect on TFP. This negative impact increases as the share of exports, imports, and FDI in the sector intensifies. Investment and export promotion policies should be tailored based on the technology intensity (low, medium, and medium-high) as the effects of FDI and export participation differ across industries.